The Postindustrial Society, Science and Professions - Hofreiter, Roman (Communications - Scientific letters of the University of Zilina, 2007)
Our main aim is to characterize the settlement and mutations of theories of professions using also other than traditional sociological approaches to this issue. Above all, we have been inspired by conceptions formed in the area of science and technology studies. The main argument appears from the fact that enquiry into professions can possible lead to description of important mutation that characterizes the scene of work and class-divided composition of “postindustrial society”.